Acute visual deterioration and headaches in a patient with suprasellar lesion: Question. (April 2021) - León, Juan F.; Candanedo, Carlos; Kaye, Andrew H.; Cohen, José E.; Moscovici, Samuel
Highlights: Cavernous malformation should be a differential diagnosis of suprasellar lesions. Management of asymptomatic optic apparatus cavernous malformation is still debatable. The relative risk of visual deterioration after repetitive hemorrhage may be higher than the risk of surgical removal.